Genicular nerve radiofrequency ablation, phenol neurolysis or conservative medical management in patients with knee osteoarthritis: protocol for the RADIOPHENOL randomised controlled multicentre trial with three parallel groups - Markus W Hollmann; Johan Haumann; Bram Thiel; Marc B Godfried; Jan-Willem Kallewaard; Paul R de Wit; Rienk van Beek; Monique Schokker; Carin Wensing; Gezina Oei; Derk A van Kampen; Lars Elzinga; et al. (BMJ Open, 2025)
Introduction Guidelines for symptomatic knee osteoarthritis (OA) dictate the initiation of conservative treatment (physical therapy, analgesics and intra-articular injections with corticosteroids) as a first line defence. When conservative treatment fails, the golden standard is invasive joint replacement surgery, but for a substantial group of patients who do not respond to the current conservative treatment, this is not (yet) indicated. The RADIOPHENOL study investigates if denervation of knee sensory (genicular) nerves can serve the gap between conservative and invasive treatment for younger patients and for patients who cannot undergo joint replacement surgery due to comorbid health conditions.Methods and analysis The RADIOPHENOL study is a multicentre unblinded randomised controlled trial with three parallel arms (1:1:1). In total, 192 patients with knee OA Kellgren-Lawrence grades 2–4 but not eligible for joint replacement according to the orthopaedic surgeon due to young age, old age and/or comorbidity or technical reasons are eligible and will be randomised to three groups of 64 patients. Group A: traditional radiofrequency ablation, group B: chemical neurolysis with phenol, group C: conservative medical management. Primary outcome is the Oxford Knee Score at 6 months. Secondary outcomes include Western Ontario and McMaster Universities Osteoarthritis Index, knee pain by numeric rating scale, physical functionality, health-related quality of life, mental health, change in medication use, predictive value of a diagnostic block, procedure time, patient discomfort score during the intervention and adverse events.Ethics and dissemination The protocol (V.2.0, 15 May 2023), was approved by the Ethics Committee of Amsterdam UMC (NL83410.018.22 – METC2022.0890) on 31 July 2023. We aim to publish our results in international peer-reviewed journals.Trial registration details ClinicalTrials.gov NCT06094660, including the WHO Trial Registration data set items. Registered on 20 October 2023, first patient enrolled on 27 November 2023.